Good governance principles and their application at communal forest level. The case of Crown Range Area, Chiredzi District, Masvingo Province, Zimbabwe - Mavunganidze, Oscar (Midlands State University, 2017)
It is not yet clear which principles are being applied, how these principles are applied and what are the benefits drawn as a result of implementation of these principles, as well as the effectiveness of these principles on conservation and management of Crown Range local forest. Good governance is the order of the day in modern development circles of natural resource management. However, good governance has moved from all other areas of sustainable development to focus its main thrust on natural resource governance. This study seeks to explore the application of good forest governance principles, their effectiveness and the impacts to local people in Crown Range area, Chiredzi District in Masvingo province, Zimbabwe. The research adopted the use of interviews, questionnaires and direct observations as primary data sources while journals, books, newspaper articles and reports from Forestry Commission and Rural District Council were the secondary data sources. A sample size of 62 household representatives was selected and key informants for interviews to get a broad spectrum of information on the application of governance principles at local forest level. It emerged that Crown Range community is mainly dominated by female population who had the highest proportion of respondents from the sample as compared to the males. It also emerged that the age group of the general population have direct impact on the application of good governance. A high proportion of the respondents represented the economically active population whereas the elderly population had the least proportion of respondents. A greater proportion of the respondents revealed ignorance about the governance principles being applied at local forest level. Therefore with such information one can safely conclude that there are still loopholes in the implementation of good governance principles in local forest governance. The parties involved are recommended to integrate their actions towards mobilizing adequate resources and implementation of governance principles.